Evaluation of Usefulness of the Designed Laboratory Photobioreactor for Microalgae Cultivation in Controlled Conditions (Agricultural Engineering, 2016)
The objective of the paper was to analyse the use of the designed photobioreactor for freshwater microalgae cultivation in the controlled laboratory conditions. The work covered the design and construction of photobioreactors (PBR) and setting up comparative cultivations of freshwater microalgae chlorelli vulgaris along with determination of the biomass growth intensity for a varied amount of supplied culture medium. It was found out that the constructed PBR may be used for microalgae cultivation in the controlled conditions. The impact of the culture medium amount on the growth of chlorelli vulgaris was proved. As a result of the increase of culture medium concentration to 30.1-120.4 ml·l−1 of water, dry mass in photobioreactorsincreased respectively from 1.33 g·dm−3 to 4.68 g·dm−3.